Supratrochlear Rim Is Correlated With Isolated Patellar Chondromalacia on Magnetic Resonance Imaging of the Knee - Artur Banach, Ph.D; Nobuhiko Hata, Ph.D; Ross Crawford, M.D., Ph.D; Tomasz Piontek, M.D., Ph.D (Elsevier, 2024)
Purpose: To investigate the relationship between the supratrochlear rim and isolated patellar chondromalacia (PC) using magnetic resonance imaging (MRI) scans of the knee. Methods: Patients without patellofemoral pain (control group) and patients with patellofemoral pain and diagnosed with stage III or IV PC based on MRI (defect group) were retrospectively identified. Patients with a history of patellar subluxation were excluded. We used patient MRI scans to perform 20 anatomical measurements of the patellofemoral joint. We also performed 2 measurements of the anterior femoral curvature. A total of 30 patients (29 ± 8.7 years) were in the control group, and 20 patients were in the defect group (29.4 ± 9.7 years). Results: The maximum curvature (P < .001) and mean curvature (P < .001) of the anterior femoral condyle were found statistically significantly different between the groups. Patellotrochlear index (P = .03) and Insall-Salvati index (P < .001) were also found statistically significantly different between the 2 groups. Patella type III and trochlear dysplasia grade B were found more common in the defect group. Conclusions: We have shown through MRI knee measurements that the isolated patellar chondromalacia in patients without a history of patellar subluxation and dislocation is correlated with the increased anterior femoral curvature in combination with patella alta. Level of Evidence: Level III, progostic case-control.